Sensitive and Selective Electrochemical Detection of Epirubicin as Anticancer Drug Based on Nickel Ferrite Decorated with Gold Nanoparticles - Mohammad Mehmandoust; Nevin Erk; Ceren Karaman; Fatemeh Karimi; Sadegh Salmanpour (Micromachines, 2021)
The accurate and precise monitoring of epirubicin (EPR), one of the most widely used anticancer drugs, is significant for human and environmental health. In this context, we developed a highly sensitive electrochemical electrode for EPR detection based on nickel ferrite decorated with gold nanoparticles (Au@NiFe2O4) on the screen-printed electrode (SPE). Various spectral characteristic methods such as Fourier transform infrared spectra (FT-IR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), ultraviolet-visible spectroscopy (UV-Vis), energy-dispersive X-ray spectroscopy (EDX) and electrochemical impedance spectroscopy (EIS) were used to investigate the surface morphology and structure of the synthesized Au@NiFe2O4 nanocomposite. The novel decorated electrode exhibited a high electrocatalytic activity toward the electrooxidation of EPR, and a nanomolar limit of detection (5.3 nM) was estimated using differential pulse voltammetry (DPV) with linear concentration ranges from 0.01 to 0.7 and 0.7 to 3.6 µM. The stability, selectivity, repeatability reproducibility and reusability, with a very low electrode response detection limit, make it very appropriate for determining trace amounts of EPR in pharmaceutical and clinical preparations.